It’s What’s on the Inside That Counts: Analyzing Student Use of Sources in Composition Research Papers - Rosenzweig, James W.; Lambert, Frank; Thill, Mary C. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2021)
Objective – This study is designed to discover what kinds of sources are cited by composition students in the text of their papers and to determine what types of sources are used most frequently. It also examines the relationship of bibliographies to in-text citations to determine whether students “pad” their bibliographies with traditional academic sources not used in the text of their papers.Methods – The study employs a novel method grounded in multidisciplinary research, which the authors used to tally 1,652 in-text citations from a sample of 71 student papers gathered from English Composition II courses at three universities in the United States. These data were then compared against the papers’ bibliographic references, which had previously been categorized using the WHY Method. Results – The results indicate that students rely primarily on traditional academic and journalistic sources in their writing, but also incorporate a significant and diverse array of other kinds of source material. The findings identify a strong institutional effect on student source use, as well as the average number and type of in-text citations, which demographic characteristics do not explain. Additionally, the study demonstrates that student bibliographies are highly predictive of in-text source selection, and that students do not exhibit a pattern of “padding” bibliographies with academic sources.Conclusion – The data warrant the conclusions that an understanding of one’s own institution is vitally important for effective work with students regarding their source selection, and that close analysis of student bibliographies gives an unexpectedly reliable picture of the types and proportions of sources cited in student writing.